Experimental study of ductility adequacy on interior wall-slab joint subjected to lateral cyclic loading / Mohd Ashaari Masrom - Masrom, Mohd Ashaari; Abdul Hamid, Nor Hayati; Mohamad, Mohd Elfie (Universiti Teknologi MARA Cawangan Pulau Pinang, 2017)
In Malaysia, the tunnel-form building has been utilised in building construction since 1980 in the construction of high-rise residential house such as condominium and apartment. Most of the tunnel-form buildings have been designed according to British Standard (BS) whereby there is no provision for seismic loading. The high-rise tunnel-form building is vulnerable to seismic loading and the joint between slab and shear walls in tunnel-form building constitute an essential link in the out-ofplane lateral load-resisting mechanism. It is a known fact that Malaysia is no longer safe from earthquake disaster consequent to the damage of building. The ductility performance of interior wall-slab joint influences the pattern and distribution of lateral forces among the vertical elements of a structure. In line with that, this study presents the results of an experimental investigation on the ductility performance of interior wall-slab joint which is designed in accordance to BS 8110.The experiment work includes a full-scale test of wall-slab joint subassemblages under out-of-plane lateral cyclic loading. One subassemblage specimen of the interior wall-slab joint was designed and constructed according to the code. The specimen was tested based on lateral displacement control (drift control). It was found that the specimen is able to survive up to 1.5% drift. The analysis results indicate that the specimen was governed by brittle failure modes with ductility class low (DCL) as stated in Eurocode 8 (EC8). This resulted from insufficient reinforcement provided. Consequently, the specimen was unable to dissipate sufficient energy to sustain longer in the inelastic zone.